Arterial stiffness and sedentary lifestyle: Role of oxidative stress - Lessiani, Gianfranco; Santilli, Francesca; Boccatonda, Andrea; Iodice, Pierpaolo; Liani, Rossella; Tripaldi, Romina; Saggini, Raoul; Davì, Giovanni (Vascular pharmacology, 2016)
Sedentary lifestyle is a risk factor for the development of cardiovascular disease, and leads to a quantifiable impairment in vascular function and arterial wall stiffening. We tested the hypothesis of oxidative stress as a determinant of arterial stiffness (AS) in physically inactive subjects, and challenged the reversibility of these processes after the completion of an eight-week, high-intensity exercise training (ET). AS was assessed before and after ET, measuring carotid to femoral pulse wave velocity (PWV) with a Vicorder device. At baseline and after ET, participants performed urine collection and underwent fasting blood sampling. Urinary 8-iso-PGF2α, an in vivo marker of lipid peroxidation, total, HDL and LDL cholesterol, and triglyceride concentrations were measured. ET was associated with significantly reduced urinary 8-iso-PGF2α(p<0.0001) levels. PWV was significantly reduced after ET completion (p<0.0001), and was directly related to urinary 8-iso-PGF2α(Rho=0.383, p=0.021). After ET, cardiovascular fitness improved [peak oxygen consumption (p<0.0001), peak heart rate (p<0.0001)]. However, no improvement in lipid profile was observed, apart from a significant reduction of triglycerides (p=0.022). PWV and triglycerides were significantly related (Rho=0.466, p=0.005) throughout the study period. PWV levels were also related to urinary 8-iso-PGF2α in our previously sedentary subjects. We conclude that regular physical exercise may be a natural antioxidant strategy, lowering oxidant stress and thereby the AS degree. [Display omitted]